(3JgPjH GdCNdGb hJWgjQ GdCYQGbs - (3CMeO Hf eMeO Hf jYbhH perSncnhrjg, CHh Ydj,J (B421 (3g` s
(3ChdgG (B:s
(3cd LSe dg UhQI hdjS jbHd UhQI CNQi ef LfS UhQJg s
(3BNQgG (B:s
(3hai GdCTjGA GdVGQI HGdYcS aEfg jWdH GdfbUGf dfaSg hGdRjGOI dZjQg ajgG gPG BNQ eG hLO s
(3Vef eLehY , JQJjHgG (B: (3GdKGfis
(3GfXQg eY GdeNWhW Qbe (B259s
(3bdjd GdEYLGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B168s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B- (3cdjI Mbhb (B(112 - (3H(B) s
Keywords: (3GdadSaI hGdefWbs